ANAOSIS PENGARUH KESEMPATAN KERJA, TINGKAT BEBAN/TANGGUNGAN DAN PENDIDIKAN TINGGITERHADAP PENGANGGURAN DI PROPINSI DATI I JAWATENGAH - Daryono Soebagiyo (Muhammadiyah University Press, 2005)
This research will analyze the effect of employment level, load level/other citizen burden, and high education toward unemployment in Central Java Province. The aims of this research are to analyze whether employment rate, depencency ratio and high education level have any effect toward unemployment in Central Java Province, and to reveal how far the effect of each variables; that are employment rate, depencency ratio and high education level, on short period and long period unemployment in Central Java Province.In this analysis, the writer concludes that no independent variable used has significant effect toward the dependent variable, i.e. unemployment. This may be happened because people with high education tend to search for a job not only in this province but also to others that have leading sector according to the major he has, and the higher education he has the burden ratio will not influence unemployment, whether in short term or long term.